Globalizing the Department to Expand Students’ Cultural and World Awareness - Jon K Dalager (Academic Chairpersons Conference Proceedings, 2017)
Advances in technology and the development of a world economy requires all academic departments to prepare their students for life in a globalized world. This session presents specific ideas on how chairs can globalize their department, curriculum, and campus.
Keywords: Global; international; study abroad; programs; world